2020
DOI: 10.1186/s13007-020-00592-7
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens mediated transformation of the aquatic carnivorous plant Utricularia gibba

Abstract: Background: The genus Utricularia belongs to Lentibulariaceae, the largest family of carnivorous plants, which includes terrestrial, epiphytic and aquatic species. The development of specialized structures that evolved for carnivory is a feature of this genus that has been of great interest to biologists since Darwin's early studies. Utricularia gibba is itself an aquatic plant with sophisticated bladder traps having one of the most complex suction mechanisms for trapping prey. However, the molecular character… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, five articles about genetic transformation of carnivorous plants are available (Hirsikorpi et al 2002 ; Królicka et al 2010 ; Blehova et al 2015 ; Miguel et al 2019 ; Oropeza-Aburto et al 2020 ), while only one is about transformation with wild strains of R. rhizogenes bacteria (Królicka et al 2010 ). Hirsikorpi et al ( 2002 ) and Oropeza-Aburto et al ( 2020 ) used Rhizobium tumefaciens (former: Agrobacterium tumefaciens ) as a vector organism, while in the work of Blehova et al ( 2015 ), R. rhizogenes with green fluorescent protein gene served for Drosera rotundifolia L. transformation. Furthermore, Miguel et al ( 2019 ) explored virus-based plant transformation to create transgenic sundew and pitcher plants, for the overproduction of recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, five articles about genetic transformation of carnivorous plants are available (Hirsikorpi et al 2002 ; Królicka et al 2010 ; Blehova et al 2015 ; Miguel et al 2019 ; Oropeza-Aburto et al 2020 ), while only one is about transformation with wild strains of R. rhizogenes bacteria (Królicka et al 2010 ). Hirsikorpi et al ( 2002 ) and Oropeza-Aburto et al ( 2020 ) used Rhizobium tumefaciens (former: Agrobacterium tumefaciens ) as a vector organism, while in the work of Blehova et al ( 2015 ), R. rhizogenes with green fluorescent protein gene served for Drosera rotundifolia L. transformation. Furthermore, Miguel et al ( 2019 ) explored virus-based plant transformation to create transgenic sundew and pitcher plants, for the overproduction of recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, five articles about genetic transformation of carnivorous plants are available (Hirsikorpi et al 2002;Królicka et al 2010;Blehova et al 2015;Miguel et al 2019;Oropeza-Aburto et al 2020), while only one is about transformation with wild strains of R. rhizogenes bacteria (Królicka et al 2010). Hirsikorpi et al (2002) and Oropeza-Aburto et al 2020 It was shown by Franklin et al (2008) on the Hypericum perforatum L. model that the most limiting factor in successful genetic transformation of plants using Rhizobium bacteria is plant's recalcitrance.…”
Section: Discussionmentioning
confidence: 99%
“…The tremendous progress seen in Arabidopsis is, in part, attributed to the ease at which this plant can be genetically transformed, allowing various genes for leaf development to be functionally validated. Recent progress in this direction, such as the establishment of Agrobacterium -mediated transformation protocols in N. mirabilis ( Miguel et al, 2020 ) and U. gibba ( Oropeza-Aburto et al, 2020 ), offers much-needed hope for a complete genetic dissection of these complex leaf shapes.…”
Section: Discussionmentioning
confidence: 99%
“…Biological research in this field has long been hampered by the lack of powerful, efficient tools to analyze gene function in vivo. Recent advances in transgenic techniques (Lee et al 2019;Mano et al 2014;Oropeza-Aburto et al 2020;Suda et al 2020)…”
Section: Discussionmentioning
confidence: 99%